Laboratory assessment of liver function in people starting antiretroviral therapy with Dolutegravir or Efavirenz: a cohort study in Belo Horizonte, Brazil (Research, Society and Development, 2022)
Objective: to verify which antiretroviral treatment regimen was safer for people living with HIV, dolutegravir 50mg + lamivudine 300mg + tenofovir 300mg or efavirenz 600mg + lamivudine 300mg + tenofovir 300mg. For this, the following laboratory tests of liver function were analyzed: total, direct and indirect bilirubin, aspartate amino transferase, alanine amino transferase, gamma glutamyl transferase and alkaline phosphatase. Methodology: cohort study, with the follow-up of 234 people living with HIV and starting antiretroviral therapy in the city of Belo Horizonte, Minas Gerais, Brazil, with data collected between August 2015 and December 2018. Results: Mean values for the results of total and indirect bilirubin, aspartate amino transferase, alanine amino transferase and alkaline phosphatase tests reduced after 72 weeks for the two therapeutic regimens. The mean value for direct bilirubin in people taking efavirenz increased at 72 weeks and was above baseline compared to baseline. For gamma glutamyl transferase, the mean of the results was above the reference value in both groups before treatment. After 72 weeks of therapy with dolutegravir, the mean returned to baseline and, in the case of efavirenz, the mean remained high. Bonett's and Dunnett's tests had no statistical difference, indicating that the two therapeutic regimens are safe. Conclusions: the two therapeutic regimens studied proved to be safe and did not cause an increase in the variance for laboratory tests that were markers of liver function.